PERSEPSI PEMANGKU KEPENTINGAN TERHADAP KEBIJAKAN ALIHFUNGSI LAHAN DI KOTA TASIKMALAYA - Dede Sudrajat; Trisna Insan Noor; Iwan Setiawan; Maman Haeruman Karmana (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
The conversion of land functions not only reduces the area of agricultural land, but reduces the number of smallholders significantly. The research objective is to strengthen the implementation of stakeholder policies on land conversion so that it can support food security programs through sustainable food land protection. This research was designed quantitatively by using a survey method with the technique of collecting information through interviews, field observations and documentation. Data obtained from informants who can present who can find out about the land conversion that occurred in the City of Tasikmalaya. The results showed 1) Stakeholders' perceptions state the importance of maintaining food agriculture in Tasikmalaya City, meaning that an urban area does not depend entirely on food imports, because it is able to meet food needs independently. 2) The perception of stakeholders that the conversion of paddy fields in Tasikmalaya City is happening is very high, the conversion of agricultural land to land use depends on the reference of development actors in urban areas.